2013
DOI: 10.1182/blood.v122.21.109.109
|View full text |Cite
|
Sign up to set email alerts
|

Aurora A Kinase Is a Novel Therapeutic Target In The Myeloproliferative Neoplasms

Abstract: We recently reported that the induction of polyploidization of malignant megakaryocytes shows great promise as a new therapy for acute leukemia. Polyploidization inducers such as dimethylfasudil (diMF) and MLN8237, both of which target Aurora A kinase (AURKA), induce proliferation arrest, polyploidization, expression of megakaryocyte differentiation markers and apoptosis of leukemic megakaryocytes in vitro and in vivo. Since megakaryocytes in primary myelofibrosis (PMF) show impaired polyploidization and matur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Recent experiments have demonstrated that activation of c-Jun, a gene downstream to TGF-β, induces fibrosis in multiple organs, including bone marrow (BM) and lung, in mice 24,25 . In the case of myelofibrosis (MF), the most severe of the Philadelphia-chromosome negative myeloproliferative neoplasms 26,27 , c-jun is activated by increased microenvironment bioavailability of TGF-β produced by abnormal megakaryocytes 28,29 . In fact, the MK in the BM of patients with myelofibrosis remain immature due to a RSP14 ribosomopathy induced by the driver mutations that reduces the translation of the mRNA for GATA1 30,31 , the transcription factor essential for their proper maturation 32 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent experiments have demonstrated that activation of c-Jun, a gene downstream to TGF-β, induces fibrosis in multiple organs, including bone marrow (BM) and lung, in mice 24,25 . In the case of myelofibrosis (MF), the most severe of the Philadelphia-chromosome negative myeloproliferative neoplasms 26,27 , c-jun is activated by increased microenvironment bioavailability of TGF-β produced by abnormal megakaryocytes 28,29 . In fact, the MK in the BM of patients with myelofibrosis remain immature due to a RSP14 ribosomopathy induced by the driver mutations that reduces the translation of the mRNA for GATA1 30,31 , the transcription factor essential for their proper maturation 32 .…”
Section: Introductionmentioning
confidence: 99%